Identifying Tourist Places of Interest Based on Digital Imprints: Towards a Sustainable Smart City - Encalada, Luis (2017)
As cities become increasingly complex, Information and Communication Technologies (ICTs) bring smartness into organisations and communities, contributing to a more competitive tourism destination, i.e., smart tourism destinations. Enhanced information access coupled with a new kind of tourists avid for online content and predisposed to share information on social media, allows for a better understanding of tourist behaviour regarding their spatial distribution in urban destinations. Thus, smart tourism portrays individuals as information makers, reﬁning the available alternativesfortrackingtheirlocation. Bigdataanalyticsisatechnologywiththepotentialtodevelop SmartCityservices. FromtheanalysisofthespatialdistributionoftouristsinthecityofLisbonbased on data collected from the ‘Panoramio’ social network, we identify the most popular places in the cityinacontextoftouristvisits. Thisnewdatalargelycontributestounderstandingtheconsumption of space within urban tourist destinations and therefore enables us to differentiate the overcrowded places from the ones with potential to grow. This allows decision-makers to imagine new ways of planning and managing towards a sustainable ‘smart’ future.